HUBUNGAN PLAK DENGAN STATUS GINGIVA PADA SISWA SMP N 1 BANUHAMPU KABUPATEN AGAM - Yustina Sriani (Ensiklopedia of Journal, 2019)
The dental plaque becomes the main problem into tooth and mouth. It can cause toothache ans sore mouth. Plaque has become an important thing in the soft inflammation process around the teeth, one of them is gingivitis. Type of the research is Descriptive Analytic with Cross Sectional Approach. The statistical test uses “Product Moment Pearson”. This research was conducted on March 8, 2018. The populations of this study are the students of SMP N 1 Banuhampu which amounted 156 students, while the sample of research consists of 54 respondents. The sampling is done by using technique “Simple Random Sampling”. The results of the research showed 46% for the highest plaque index and 6% the lowest plaque value. There are 48% the highest gingival status that was obtained on the light inflammatory criteria an it is about 15% the lowest. The result of statistical test shows that p value 0,00 < 0,05 so there is average correlation (r = 0,483) with positive scheme, when plaque index is higher then gingiva inflmmation is higher too. For the conclusion, there is a significant relationship between plaque with gingival status. The meaning is more plaque in the tooth that cause the higher inflammation of the gingiva. Therefore it is suggested to respondents to maintain the hygiene of tooth and mouth by brushing teeth at least twice a day, in the morning after breakfast and in the night before bed and visit dental and oral care unit at least 1x6 months.